Growth, economic development and structural transition in small vulnerable states - Robert Read (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2001)
This paper reviews the critical theoretical and policy issues relating to growth, economic development and structural transition in small states. The paper discusses alternative perspectives on small size and highlights the salient characteristics which give rise to their economic sub-optimality. The theoretical and empirical relationship between size and growth is reviewed, including recent inferences relating to structural transition and comparative advantage in small states. This discussion derives several insights from endogenous growth theory and highlights the critical role of available endogenous policy options, particularly with respect to trade and its implications for the process of growth and development. The discussion of vulnerability touches upon methodological and data issues relating to measurement, provides a critique of alternative indices and the impact of vulnerability in small states.
Keywords: O40; O56; O57; 330; small states; micro-states; growth; vulnerability; development; policy strategies; Kleinstaat; Wirtschaftswachstum; Entwicklung; Welt